2016
DOI: 10.1093/mnras/stw1495
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy And Mass Assembly (GAMA): $\mathcal {M_\star }\text{--}R_{\rm e}$ relations ofz= 0 bulges, discs and spheroids

Abstract: We perform automated bulge + disc decomposition on a sample of ∼7500 galaxies from the Galaxy And Mass Assembly (GAMA) survey in the redshift range of 0.002 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
136
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(160 citation statements)
references
References 112 publications
24
136
0
Order By: Relevance
“…Lange et al 2016). Galaxies that never suffered an instability in their existence, however, meet the observed relation quite precisely.…”
Section: Caveats Discussion and Conclusionmentioning
confidence: 55%
“…Lange et al 2016). Galaxies that never suffered an instability in their existence, however, meet the observed relation quite precisely.…”
Section: Caveats Discussion and Conclusionmentioning
confidence: 55%
“…Combining the visual morphological classifications of GAMA sources with z0.06 presented by Kelvin et al (2014) and the bulge-disk decompositions of this sample presented by Lange et al (2016) and cross-matching with our samples using GAMA's unique source identifier, we find an average r-band B/T value of B/T=0.3 (0.18) in the high (low) stellar mass range of the FIELDGALAXY sample and a comparable value of B/T=0.32 (0.19) for those galaxies in the FIELDGALAXY parent sample visually classified as S0/SaSd/Irr. As fading will only act to increase the B/T ratio, we restrict ourselves to considering the high stellar mass range as our fiducial galaxy.…”
Section: Appendix a Selection Of Disk/spiral Galaxiesmentioning
confidence: 68%
“…Distribution of r-band B/T values for GAMA sources in the FIELDGALAXY (red) and FIELDGALAXY parent sample (gray) with z0.06 as determined by Lange et al (2016). Those members of the FIELDGALAXY parent sample visually classified (Kelvin et al 2014) as Sab-Sd/Irr galaxies are shown in blue, while the superset additionally including S0/Sa galaxies is shown in green.…”
Section: Appendix B Deriving Attenuation Correctionsmentioning
confidence: 99%
“…The right panel shows the half-mass radius of stars, considering both the bulge and disk components, for disk-dominated, star forming galaxies only (sSF R > 0.3/t H , M bulge /M⋆ < 0.5). The diamonds with error bars and triangles in the middle panel are observed stellar disk sizes based on SDSS and GAMA (Dutton et al 2011;Lange et al 2016, half-light radius for disk only). The triangles are observed sizes based on GAMA data (Lange et al 2015, half-light radius for disk and bulge).…”
Section: Appendix B: Resolution Testsmentioning
confidence: 99%